Analisis Pengelolaan Sampah Pada Masyarakat Di Nagori Karang Rejo Kecamatan Gunung Maligas Kabupaten Simalungun - Eka SR. Sihombing; Nur Masdalifah; Anggun Dewi Maharani; Ridho Adha (Politeknik Ganesha Medan, 2025)
Waste management is an urgent environmental issue that requires addressing, especially in rural areas with minimal waste management facilities. This qualitative study, involving 20 informants, including village officials and the community, aims to analyze the waste management system of the Karang Rejo community in Nagori, Gunung Maligas District, Simalungun Regency. A descriptive qualitative approach was used to gather information through interviews, observation, and documentation. The results indicate that waste management in this area is suboptimal. Residents generally burn or dispose of waste in rivers and yards due to the lack of temporary waste disposal sites (TPS) and transportation facilities. Furthermore, public awareness of the environmental and health impacts of waste remains low. This study recommends improving waste management infrastructure and public education to support sustainable and environmentally conscious waste management.